Morphological and molecular evidence of the occurrence of Artibeus amplus (Chiroptera: Phyllostomidae) in Brazil - Marlon Zortéa; Maria Clara Santos Ribeiro; Paola Santos da Mata; Cibele Rodrigues Bonvicino (Zoologia (Curitiba))
ABSTRACT Artibeus amplus Handley, 1987 is a little-known bat species endemic to northern South America. There are confirmed records of the species for Colombia, Venezuela, Guyana, and Suriname. In this study, we report the occurrence of A. amplus in Brazil based on the collection of two specimens captured in the municipalities of Cantá and Caracaraí in the state of Roraima. We also found a museum specimen from the state of Amazonas. The specimens were identified based on morphology and mitochondrial Cytochrome b gene analysis. After this contribution, the number of bat species in Brazil is 182. Surveys in other areas in the north of the country, such as the state of Pará, in addition to a comprehensive review of museum specimens, is needed to investigate the distribution of the species in areas where it has not been found yet.